Colombia's Universal Health Insurance System - Giedion, U.; Uribe, M. V. (2012)
By insuring more than 80 percent of its population, Colombia provides a valuable opportunity to gather evidence on a hotly debated health policy issue. Results from three studies evaluating the impact of universal health insurance in Colombia show that it has greatly increased access to and use of health services, even those that are free for all, and has reduced the incidence of catastrophic health spending. The impact has been more dramatic among those most vulnerable to health shocks: those living in rural areas, the poorest, and the self-employed. [Health Affairs 28, no. 3 (2009): 853-863; 10.1377/hlthaff.28.3.853]